Management of damping-off disease of opium poppy - and K.K. JANARDHANAN, M. ALAM, A. SATTAR (Indian Phytopathology, 2002)
The efficacy of 5 fungicide treatments, metalaxyl + mancozeb, fosetyl-Al [fosetyl], captan, propamocarb hydrochloride [propamocarb] and triadimefon, was tested in vitro against the growth of Pythium dissotocum causing damping-off of opium poppy (Papaver somniferum). Metalaxyl + mancozeb was highly effective, showing 50% growth inhibition at 7éŽ”/ml a.i. of both the constituents. Seed treatment with the same fungicide at 0.12 g.a.i./100 g seed (cv. Shyama) gave 100% disease control, with seedling emergence equivalent to steam sterilized soil. Seed treatment with captan at 0.3% or soil drenching with propamocarb hydrochloride at 0.3% were the next most effective treatments showing 75% seedling emergence as compared with 2.7% seedling emergence in the untreated control. In pathogenicity tests on 5 varieties and 11 mutants of opium poppy under glasshouse conditions, variety IS-42 and mutant S-102 were highly resistant to damping-off. It is concluded that damping-off of opium poppy could be effectively managed either by seed treatment with metalaxyl + mancozeb or by the use of resistant varieties.